The stolen Bible : from tool of imperialism to African icon - West, Gerald O. (Biblical Interpretation Series, 2016)
The Stolen Bible tells the story of how Southern Africans have interacted with the Bible from its arrival in Dutch imperial ships in the mid-1600s through to contemporary post-apartheid South Africa. The Stolen Bible emphasises African agency and distinguishes between African receptions of the Bible and African receptions of missionary-colonial Christianity. Through a series of detailed historical, geographical, and hermeneutical case-studies the book analyses Southern African receptions of the Bible, including the earliest African encounters with the Bible, the translation of the Bible into an African language, the appropriation of the Bible by African Independent Churches, the use of the Bible in the Black liberation struggle, and the ways in which the Bible is embodied in the lives of ordinary Africans.